2020
DOI: 10.14203/beritabiologi.v19i3a.3933
|View full text |Cite
|
Sign up to set email alerts
|

SELECTIVE ISOLATION OF Dactylosporangium AND Micromonospora FROM THE SOIL OF KARST CAVE OF SIMEULUE ISLAND AND THEIR ANTIBACTERIAL POTENCY

Abstract: Karst is a unique ecosystem that consists of a thin soil layer on the carbonate rocks. It has a diverse microorganism, especially actinomycetes group, which might potentially produce beneficial secondary metabolites that remain unknown. In this study, we were interested in isolating Dactylosporangium and Micromonospora that have been potentially reported as antibiotic sources. We used two methods using the chemical germicide (pretreatment 1.5% phenol) compared with the SDS-YE (0.05% SDS pretreatment). Thirty-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Enggano Island, North Bengkulu Province, is Indonesia's outermost island located in the Indian Ocean. The island is composed of weak wavy hills, karst hills, soils, and swamps, whereas the mainland area is dominated by cambisol, and alluvial soil types, with thick texture plates [8]. The diverse characteristics of the land cause the island to have a unique ecosystem.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enggano Island, North Bengkulu Province, is Indonesia's outermost island located in the Indian Ocean. The island is composed of weak wavy hills, karst hills, soils, and swamps, whereas the mainland area is dominated by cambisol, and alluvial soil types, with thick texture plates [8]. The diverse characteristics of the land cause the island to have a unique ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…The diverse characteristics of the land cause the island to have a unique ecosystem. The differences in environmental conditions, climate, and ecology, will affect the type of microbes in Enggano Island including the actinomycetes group [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurkanto (2007) reported that some kinds of actinomycetes are capable of solubilizing phosphate, including member genera Nocardia sp., Streptomyces, Micromonospora sp., Actinoplanes sp., Microbispora sp., Microtetraspora and Streptosporagium sp. Putri and Sumerta (2020) also found about eleven genera of actinomycetes from the karst cave soils of Simeulue island, one of which is Streptomyces. Streptomyces griseorubens BC10 and Nocardiopsis alba BC11 are promising candidates as phosphate solubilizing bacteria (Boubekri et al 2021).…”
Section: Discussionmentioning
confidence: 97%
“…Plants in the karst ecosystem, bacteria were found associated with bacteria in their root systems, including actinomycetes and non-actinomycetes groups. According to Putri and Sumerta (2020), there are 11 genera of actinomycetes found in the karst ecosystem of Semeulue Island. Elshafie and Camele (2022), also reported that the root system of rosemary, acacia, strawberry, and olive was associated with some kinds of actinomycetes strains.…”
Section: Discussionmentioning
confidence: 99%